The Effect of Age Diversity in Groups on Peer Evaluations and Individual Performance - Katja Görlitz; Tim Sels (Institute of Labor Economics (IZA), 2021)
This study analyzes how individuals evaluate their peers' performance in a high stakes tournament in response to being randomly assigned to an age homogenous or heterogeneous group using data from two TV shows. The data also allows us to explore superior evaluations because it contains objective ratings from an independent expert. Additionally, this study investigates how age diverse groups affect individual performance in professional golf tournaments. The results show that peer and superior evaluations as well as individual performance are lower in age diverse groups. Further evidence suggests that these effects occur in the short run, but fade away once group members have gotten to know each other.
Keywords: J14; M12; M54; 330; age diversity; peer evaluation; superior evaluation; performance